The Cultural District Between Planning and Spontaneity: The Agglomeration Dynamics in Manifattura delle Arti in Bologna - Liola Urso; Valeria Morea (European Journal of Creative Practices in Cities and Landscapes)
Cultural clusters are renowned to bring many benefits in terms of agglomeration and therefore they are often employed as catalysts of urban regeneration. Policymakers attempted to recreate this phenomenon through top-down strategies. However, it has been observed that clusters often arise naturally without direct intervention from local governments or policy incentives. Therefore, the policy dilemma of whether it is possible to plan something that tends to emerge spontaneously arises. Drawing on urban and cultural policy issues, this article aims at investigating the agglomeration dynamics within the planned district Manifattura delle Arti in Bologna. Through 14 interviews with the key actors involved in the district, two main findings are unveiled: the presence of a spontaneous subcluster of bottom-up organizations within the planned district and the civil society as an engine of regeneration and inclusion.